(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Four new species of Scelionid wasps (Hymenoptera) are described, all of them from Rhopalid (Heteroptera) bugs collected in Sicily: Telenomus foveatus n. sp., and bred from an unidentified species of Rhopalid, Telenomus liorhyssi n. sp. from Liorhyssus hyalinus F., Telenomus eleuterus n. sp. from Stictopleurus punctatonervosus (Goeze), and Telenomus inulae n. sp. from an unidentified Rhopalid. Telenomus minutus (Westwood) is re-described and new data is given about Rachelia robertae Mineo and Gryon nr. gnidum (Nixon).